2012
DOI: 10.1128/jvi.06893-11
|View full text |Cite
|
Sign up to set email alerts
|

UCLA1, a Synthetic Derivative of a gp120 RNA Aptamer, Inhibits Entry of Human Immunodeficiency Virus Type 1 Subtype C

Abstract: dEntry of human immunodeficiency virus type 1 (HIV-1) into cells is mediated by the virion surface envelope (Env) glycoproteins, making it a desirable target for antiretroviral entry inhibitors. We previously isolated a family of gp120 binding RNA aptamers and showed that they neutralized the infectivity of HIV-1. In this study, we assessed the activity of a shortened synthetic derivative of the B40 aptamer, called UCLA1, against a large panel of HIV-1 subtype C viruses. UCLA1 tightly bound to a consensus HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 59 publications
0
50
0
Order By: Relevance
“…It was also shown that B40 aptamer at maximum concentration of 2 µM had no cytotoxic effect on cardiomyocytes and PBMC (Lopes de Campos et al, 2009). In order to enhance biological stability of the aptamer B40, a series of minimized B40 analogs containing different chemical modifications were generated (Cohen et al, 2008; Moore et al, 2011a; Mufhandu et al, 2012). The authors suggest that the combination of such modified aptamers with nuclease-inhibiting Zn 2+ ions that are able to enhance antiviral effect of chemically modified aptamers could be applied as a basis for the antiviral drug for topical application.…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…It was also shown that B40 aptamer at maximum concentration of 2 µM had no cytotoxic effect on cardiomyocytes and PBMC (Lopes de Campos et al, 2009). In order to enhance biological stability of the aptamer B40, a series of minimized B40 analogs containing different chemical modifications were generated (Cohen et al, 2008; Moore et al, 2011a; Mufhandu et al, 2012). The authors suggest that the combination of such modified aptamers with nuclease-inhibiting Zn 2+ ions that are able to enhance antiviral effect of chemically modified aptamers could be applied as a basis for the antiviral drug for topical application.…”
Section: Antiviral Aptamersmentioning
confidence: 99%
“…Nevertheless, aptamers can effectively bind viral capsid proteins. Such binding inhibits the interaction between viruses and cellular receptors and prevents viral entry into the cell [98, 99]. It makes the potential application of aptamers for antiviral prophylaxis or therapy much easier: aptamers can be injected intravenously or applied on the skin as a solution or ointment.…”
Section: Current Status Of Aptamers In Diagnostics and Theraphymentioning
confidence: 99%
“…Thus, we previously isolated aptamers against recombinant monomeric gp120 that showed efficacy against HIV-1 in cell based assays [7][8][9][10] and had no cytotoxic side effects [11]. However, it has been observed that recombinant gp120 and native trimeric gp120 have different antigenic properties [12].…”
Section: Introductionmentioning
confidence: 97%